Training philosophies used by the Australian men's volleyball team at the elite international level - Reynolds, L. (Journal of Australian Strength and Conditioning, 2020)
The Australian Men`s Indoor Volleyball Team also known as the "Volleroos" are ranked 13th in the world and are determined to qualify for the Tokyo Olympics 2020. Through a combination of strength, power, and prevention the coaching staff has been able to establish a healthy, well-educated, and professional program. In a three year period there has been a drastic reduction in major injuries, elevated communication amongst the team, greater player education in strength & conditioning, focus on load management and an increase in overall performance in the weights room and on court in competition. Program development for the Volleyroos in strength & conditioning has moved towards not just focusing on pure strength but also targeting specific areas most vulnerable to the sport and dedicating large sections of the workout to injury prevention. Devoting daily time to areas like the posterior chain muscles, shoulder complex and the Vastus Medialis Oblique (VMO) has allowed ongoing development, strengthening, and priming of these specific muscles for volleyball. Along with this specificity there has been a focus on modification for individuals in the weights room that suffer from injuries or physical deficiencies, these changes ensure the athlete`s goals are met and weak points strengthened over the period of a season. Attention to detail when programming is essential in developing a system where individual players can gain the most out of each session and the overall team can develop in the appropriate direction. Detail orientation also needs to apply to communication with coaches and players allowing for greater customised programming and a healthier team.